2018
DOI: 10.1177/0883911518819600
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of conductive poly-dl-lactic-acid/tetra-aniline conduit for peripheral nerve regeneration

Abstract: Defected peripheral nerve regeneration is still a challenge in clinical treatment. Conductive polymers show great potential in nerve tissue engineering because of their electrical property based on bioelectricity in vivo. In this study, conductive composite nerve conduit was synthesized with tetra-aniline and poly-dl-lactic acid. Their properties and the differentiation of rat pheochromocytoma 12 (PC12) cells in vitro stimulated with 200 mV for 1 h were investigated. Different amounts of tetra-aniline (0%, 5%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…12 Guo et al synthesized a conductive composite nerve conduit from tetra-aniline and poly(DL-lactic acid) with 200 mV in vitro stimulation for 1 h to observe rat pheochromocytoma 12 (PC12) cell differentiation, showing that as the content of tetra-aniline increased, the percentage of adherent neurons on the conduit and the median length of the neurons both increased. 13 Sara et al controlled the conductivity and morphology of scaffolds by changing the polyaniline−chlorine concentration in chitosan (CS) and the scaffold preparation methods (air drying and freeze-drying), respectively, to study the effect on NIH/3T3 (mixed, fibroblasts) and PC-12 (electrical response, neuroprogenitor) cell growth, which revealed that nanofeatures of air-dried bio-nanocomposites could promote PC-12 cell growth and that PC-12 cells responded more strongly to conductive substrates than NIH/ 3T3 cells, with higher neurite outgrowth and stretching speed. 14 In order to solve the problems of intensity mismatch and inflammation of the nerve scaffold, Xu et al coated polypyrrole and CS on the surface of a poly(L-lactide)− polycaprolactone electrospun nanofiber membrane by electro-chemical deposition and in situ doping, and PC12 cells were stimulated with 100 mV for 2 h, indicating that electrical stimulation could promote the growth and arrangement of nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Guo et al synthesized a conductive composite nerve conduit from tetra-aniline and poly(DL-lactic acid) with 200 mV in vitro stimulation for 1 h to observe rat pheochromocytoma 12 (PC12) cell differentiation, showing that as the content of tetra-aniline increased, the percentage of adherent neurons on the conduit and the median length of the neurons both increased. 13 Sara et al controlled the conductivity and morphology of scaffolds by changing the polyaniline−chlorine concentration in chitosan (CS) and the scaffold preparation methods (air drying and freeze-drying), respectively, to study the effect on NIH/3T3 (mixed, fibroblasts) and PC-12 (electrical response, neuroprogenitor) cell growth, which revealed that nanofeatures of air-dried bio-nanocomposites could promote PC-12 cell growth and that PC-12 cells responded more strongly to conductive substrates than NIH/ 3T3 cells, with higher neurite outgrowth and stretching speed. 14 In order to solve the problems of intensity mismatch and inflammation of the nerve scaffold, Xu et al coated polypyrrole and CS on the surface of a poly(L-lactide)− polycaprolactone electrospun nanofiber membrane by electro-chemical deposition and in situ doping, and PC12 cells were stimulated with 100 mV for 2 h, indicating that electrical stimulation could promote the growth and arrangement of nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, endowing nerve scaffolds with certain electrical conductivity in their preparation is of special significance for adhesion, differentiation, and repair of nerve tissues . Guo et al synthesized a conductive composite nerve conduit from tetra-aniline and poly­( dl -lactic acid) with 200 mV in vitro stimulation for 1 h to observe rat pheochromo­cytoma 12 (PC12) cell differentiation, showing that as the content of tetra-aniline increased, the percentage of adherent neurons on the conduit and the median length of the neurons both increased . Sara et al controlled the conductivity and morphology of scaffolds by changing the polyaniline–chlorine concentration in chitosan (CS) and the scaffold preparation methods (air drying and freeze-drying), respectively, to study the effect on NIH/3T3 (mixed, fibroblasts) and PC-12 (electrical response, neuroprogenitor) cell growth, which revealed that nanofeatures of air-dried bio-nanocomposites could promote PC-12 cell growth and that PC-12 cells responded more strongly to conductive substrates than NIH/3T3 cells, with higher neurite outgrowth and stretching speed .…”
Section: Introductionmentioning
confidence: 99%
“…have been used in bone scaffolds for tissue regeneration. [5][6][7][8] In our previous studies, we had optimized the amount of PEDOT:PSS in certain gelatin (Gel)/ bioactive glass (BG) scaffolds and introduced Gel (10% w/v), BG (30% w/v), and PEDOT:PSS (0.3% w/w) as the best composition in terms of the material characteristics. 9,10 In this study, we have evaluated this composition by in vitro and in vivo examinations.…”
Section: Introductionmentioning
confidence: 99%